Investigation on temperature-gradient-driven effects in unconventional sintering via non-isothermal phase-field simulation. (September 2020) - Yang, Yangyiwei; Oyedeji, Timileyin David; Kühn, Patrick; Xu, Bai-Xiang
Graphical abstract: Abstract: There are still debates regarding effects driven by temperature gradient (∇ T ) during unconventional sintering, such as field assistant sintering technology and selective laser sintering, with existent analytical tools insufficient to reflect in-process features. In this work we propose a brand-new approach to investigate ∇ T -driven effects during unconventional sintering via non-isothermal phase-field simulations. 2D and 3D simulations on sintering of yttria-stabilized zirconia micro-particles not only reproduce well features investigated by analytical models, but also discover new in-process phenomena, e.g. ∇ T -induced coalescence of identical particles, and reveal potential competitions between thermophoresis and Ficktian diffusion.